FEATURES OF EVALUATING THE RATIONALITY OF CONSUMER BEHAVIOR AT ALL STAGES OF USING NON-STEROIDAL ANTI-INFLAMMATORY DRUGS IN OCCUPATIONAL DISEASES OF THE MUSCULOSKELETAL SYSTEM - Андрей Георгиевич Петров; Сергей Николаевич Филимонов; Виктор Андреевич Семенихин; Ольга Владимировна Хорошилова (Медицина в Кузбассе)
The goal is to improve the quality of medical care for occupational diseases of the musculoskeletal system using non-steroidal anti-inflammatory drugs in the formation of health for employees of the coal industry.